Sensorially accepted Mangifera indica and Myrciaria dubia yogurts with high ascorbic acid content - Barrios Renteria, Juan Carlos; Espinoza-Espinoza, Luis Alfredo; Valdiviezo-Marcelo, Jaime; Moreno-Quispe, Luz Arelis (Frontiers in Sustainable Food Systems, 2022)
Ascorbic acid deficiency in humans has been associated with an increase in acute respiratory infections, scurvy in individuals who cannot synthesize it, skin lesions and other organs, collagen deficiency, delayed wound healing, pain in the joints between other illnesses. With the objective of evaluating the content of ascorbic acid and the sensorial qualities of yoghurts from Mangifera indica and Myrciaria dubia four yogurt formulas were elaborated with different concentrations of these fruits (F1:15% and 5%; F2:15% and10%; F3: 20% yand5% y F4: 20% and 10%) respectively, compared with a sample control (Fragaria vesca yogurt at 15%). The ascorbic acid content of the different formulas was in the following order (F1: 63.2 mg/100 g; F2:114.3 mg/100 g; F3: 57.3 mg/100 g; F4: 115.1 and the control sample F5:11.5 mg/100 g), it was evidenced that the acidity level significantly influenced during the sensorial evaluation, according to the formula (F3) which presented a greater preference. These data reflect the importance of using Mangifera indica and Myrciaria dubia in the formulations, which allow it to maintain its high content of ascorbic acid and also please the consumer always and when the acidity threshold is not exceeded.